Research of a Loading of Transmissions by Flexible Link by an Integral Method - J.E. Gurevich (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2014)
The physical picture of the phenomena is considered by transfer of district effort to a belt drive by gearing or frictional at absence of elastic sliding. The model of interaction of a belt with a pulley Is offered, allowing to consider an integrated method realization of deformations - shift and stretchings - during transfer of district effort. The dependences defining change of intensity of operating loading on a belt on an arch of a grasp of a pulley are received. The estimation of loading ability of transfer depending on a design of a belt, and also the analysis of distribution of loading on an arch of a grasp of a belt in a toothed-belt drive depending on accuracy of manufacturing of a belt and the recommendation on its alignment is given.